Clinical analysis of 41 cases of antineutrophil cytoplasmic antibody associated vasculitis - GAO Qi; YANG Lin (Linchuang shenzangbing zazhi)
Objective To analyze clinical characteristics of antineutrophil cytoplasmic antibody(ANCA)-associated vasculitis(AAV).Methods A total of 41 patients with AAV admitted to China Three Gorges University from January 2012 to January 2017 were selected and analyzed.Results The ratio of male∶female was 1.05∶1,and the average age was(61.6±14.4)years old.48.4% of them were older than 65 years old.The time from disease onset to diagnosis was 5 to2 160 days,with an average of(136.68±344.79)days.Of the 41 patients,39 cases were positive for perinuclear ANCA(P-ANCA)/anti myeloperoxidase(MPO)antibody and 1 positive for cytoplasmic ANCA(C-ANCA)/anti protease 3(PR3)antibody positive,and1 negative for ANCA.The clinical manifestations of AAV were complex and varied.The manifestations of renal involvement accounted for 100%,followed by respiratory symptoms and systemic nonspecific symptoms,accounting for 61%.The degree of involvement of the lungs and kidney was different,and the time of the disease was inconsistent.The remission rate of AAV was 69.2% and the fatality rate was 9.8%.The degree of AAV involving the lung and kidney was different,and the time of the occurrence of lesions was inconsistent.Conclusions AAV involves multiple systems with varying degrees of lesions.Combination of clinical symptoms and ANCA detection is helpful for early diagnosis.Under the situation that the clinical manifestation is in accordance with AAV while the ANCA test is negative,the pathological biopsy should be done in time.The appropriate treatment is chosen after systematically assessing the degree of lesions.